Static bending of isotropic circular cylindrical shells based on the higher order shear deformation theory of Reddy and Liu - Nwoji, C.U.; Ani, D.G.; Oguaghamba, O.A.; Ibeabuchi, Victor (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a displacement based shear deformation theory formulated on the cubic in-plane displacement field equation of Reddy and Liu is presented for the static bending analysis of isotropic circular cylindrical shells. The adopted displacement field accounts for a quadratic (parabolic) distribution of the transverse shear through the shell thickness as well as satisfies the need for a stress free upper and lower boundary surfaces of the shell.
Keywords: isotropic circular cylindrical shell; shear deformation theory; transverse shear; principle of virtual work; Kirchhoff- Love theory